Eksistensi Tradisi Bersih Desa Baleturi Prambon Ngranjuk - Ramadhani, Adelia Fikriyah; Muzaiyana, Muzaiyana (Qurthuba: The Journal of History and Islamic Civilization, 2022)
The Bersih Desa tradition is a traditional activity that is carried out once a year with the aim of praying for the safety of the village and being grateful for the blessings that have been given by God. The research entitled "The Existence of the Bersih Desa Tradition (Case Study in Baleturi Village, Prambon District, Nganjuk Regency)" focuses on: 1. The history of the clean village tradition, 2. The implementation of the bersih desa tradition, and 3. Functions and elements of religion in the implementation of the tradition Baleturi Village. This research is a qualitative research with historical method. The approach used is an anthropological approach that produces descriptive data and is used to reveal the values ​​of Islamic teachings that are expressed in the bersih desa tradition in Baleturi Village. While the theory used by the author is the theory of religious ceremonies from Koentjaraningrat and the theory of functionalism from Radcliffe Brown. The results of this study indicate that: First, the bersih desa tradition is estimated to have been carried out about 50 years ago in Baleturi Village and is carried out once a year in the month of Suro. Second, a series of events in the implementation of the bersih desa tradition includes the preparation stage and the implementation stage. Third, the functions contained in this bersih desa tradition are social functions and spiritual functions. While the elements of the Islamic religion contained include deliberation, pilgrimage to the grave, tahlil and istighosah, alms, and compensation for orphans.